PHENOLIC COMPOUNDS CONTENT IN FRUITS OF DIFFERENT EGGPLANT SPECIES: S. MELONGENA L., S. AETHIOPICUM L. AND S. MACROCARPON L. - IN THE TEMPERATE CLIMATE - M. I. Mamedov; O. N. Pishnaya; Y. A. Dzhos; V. M. Verba; A. A. Matyukina (Овощи России)
In the genus Solanum there are a number of less common vegetables. S. aethiopicum L. and S. macrocarpon L. are a two popular species of eggplant, traditionally grown in tropical Africa. The object of research was breeding lines and hybrids of S. melongena L. and accessions of S. aethiopicum and S. macrocarpon. Plants were grown in condition of low-capacity hydroponics according to all agrotechnical requirements. The fruits for analysis were collected from one layer of plants at the phase of technical maturity. Phenolic compounds are unique secondary metabolites that are synthesized in all plant cells and have increasingly wide application in pharmacology and medicine. Flavonoids was in the range of 0.7-1.1% in lines and F1 hybrids of S. melongena, however more flavonoids was obtained in the African eggplant accessions, such as S. aethiopicum L., 1,4% and S. macrocarpon L., 1.2%. The total content of phenolic compounds was in the range of 1.7-2.3% in the pulp of S. melongena L. fruits. The total content of phenol carbonic acids ranged from 1.0-1.5% in the lines and hybrids F1 studied, as referred to S. melongena. The content of phenol carbonic acids is higher from 1.5% to 1.8% in S. aethiopicum and S. macrocarpon. In the pulp of the interspecific hybrid fruits the total content of flavonoids and phenol carbonic acids was 2.6-2.7% that was 1.5 times as much as in S. melongena.